Ultrastructural study of mode of entry of Chlamydia psittaci into L-929 cells. - Hodinka, R L (1986)
The entry of Chlamydia psittaci into L-929 cells was studied morphologically by transmission electron microscopy and quantitatively by a method that discriminates between attachment and uptake. Upon adsorption of 3H-labeled elementary bodies (EBs) to host cells at 4 degrees C, the EBs bound efficiently to the L-cell surface. Binding reached an equilibrium level of 55% in 3 h. Ultrastructural analysis revealed that EBs were bound preferentially to the tips and sides of microvilli at this temperature. The EBs were also observed in coated pits located at the bases of microvilli and along smooth surfaces of the host cell. No internalization was observed at 4 degrees C. When cells with prebound 3H-labeled EBs were warmed to 37 degrees C, the EBs rapidly became resistant to proteinase K removal (half time = 5 min), indicating ingested chlamydiae. At 37 degrees C, the EBs were internalized within tightly bound vesicles surrounded by an electron-dense coat of fibrillar material. EBs were also present in smooth-surfaced pits and vesicles of the host cell. Using alpha 2-macroglobulin coupled to colloidal gold (a known marker for receptor-mediated endocytosis), we observed that the entry of EBs into cells via coated pits was identical in appearance to the internalization of alpha 2-macroglobulin. Also, when the two ligands were mixed together, they could be seen within the same coated pits and were cointernalized within endocytic vesicles of the host cell. These results suggest that C. psittaci can enter nonprofessional phagocytic cells by a pathway which is similar to that of receptor-mediated endocytosis of many physiologically important macromolecules, bacterial toxins, and viruses.